A novel missense mutation T101N in the melanocortin-4 receptor gene associated with obesity - Buchbinder, Susanne; Bärtsch-Kohli, Ursula; Müller-Hennessen, Matthias; Zorn, Markus; Nawroth, Peter Paul; Schilling, Tobias (Genetics and molecular research, 2011)
Mutations in the melanocortin-4 receptor (MC4R) are associated with severe obesity, independent of their effect on cortisol or thyroid-stimulating hormone levels. We examined a morbidly obese male (BMI = 62 kg/m2) with a binge-eating disorder and eight family members for mutations in the MC4R gene and potential differences in leptin levels. Fifty healthy individuals served as controls. Sequence analysis revealed a novel heterozygous missense mutation (c.302 C>A, p.T101N) located in the second transmembrane domain of the receptor, which was not detected in controls. The Fisher exact test revealed an association between the T101N mutation and history of obesity (P < 0.05) in the family. The Kruskal-Wallis test showed an association between the mutation and the leptin/BMI ratio (P < 0.05), while there was no association between the T101N mutation and diabetes or arterial hypertension in the family. Although the available family was small, we could show a significant association between the heterozygous T101N mutation and obesity.
Gesehen am 24.06.2022